Analysis of Quality of Care Exceeding Mother's Satisfaction After Giving Birth Assisted by a Midwife - Claudia Guterres, Ana; Julieta Geri De Sena Amaral, Saturnina; Maria Ximenes, Herminia; Jesus Vaz Cabral, Teresa de; Ximenes Martins, Adelina (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: Quality of service is a service provided by health personnel to make the client or some of the community will feel satisfied with the service received in accordance with their needs. And client will be satisfied if the service they received are in line with their expectations. Based on demography health survey data in Timor-Leste in 2009/2010 showed that the maternal mortality rate was 557/100.000 live births, and the child mortality rate was 45/1.000 live births. Therefore, to reduce the mother and child mortality rate in this country, it is necessary to improve the quality of service to strengthen the trust between client and health worker to keep client closer to the nearest health family. Objective: Is Analysis the quality of service of midwifery through the satisfaction of the post partum mother on midwifery assistance during the delivery at Hospital  Regional Eduardu Ximenes Baucau. Method: The method use in this research is quantitative method. The sample in this study were all pregnant women who gave birth at certain time with a sample size of 72 people and the techniques used to determine this sample is Quota sampling technique. Results and Discusion: based on the result of the study, the majority of mothers have a good perception and are satisfied with the quality of service provided by midwives. Judging from the result that there is a positive correlation between service quality and patient satisfaction level. Conclusion: From the result of 72 respondents there is a positive relationship to the quality of service with patient satisfaction level. Therefore, the study hopes that it can provide benefits to pregnant women to be able to get closer to the nearest health facility in order to get quality services, and for midwives to always provide quality service to clients to strengthen the relationship between health workers with the community, especially to reduce maternal and infant mortality rate in Timor-Lese